Mental health before and during the COVID-19 pandemic in two longitudinal UK population cohorts. (June 2021) - Kwong, Alex S. F.; Pearson, Rebecca M.; Adams, Mark J.; Northstone, Kate; Tilling, Kate; Smith, Daniel; Fawns-Ritchie, Chloe; Bould, Helen; Warne, Naomi; Zammit, Stanley; Gunnell, David J.; Moran, Paul A.; et al.
Abstract : Background: The COVID-19 pandemic and mitigation measures are likely to have a marked effect on mental health. It is important to use longitudinal data to improve inferences. Aims: To quantify the prevalence of depression, anxiety and mental well-being before and during the COVID-19 pandemic. Also, to identify groups at risk of depression and/or anxiety during the pandemic. Method: Data were from the Avon Longitudinal Study of Parents and Children (ALSPAC) index generation ( n = 2850, mean age 28 years) and parent generation ( n = 3720, mean age 59 years), and Generation Scotland ( n = 4233, mean age 59 years). Depression was measured with the Short Mood and Feelings Questionnaire in ALSPAC and the Patient Health Questionnaire-9 in Generation Scotland. Anxiety and mental well-being were measured with the Generalised Anxiety Disorder Assessment-7 and the Short Warwick Edinburgh Mental Wellbeing Scale. Results: Depression during the pandemic was similar to pre-pandemic levels in the ALSPAC index generation, but those experiencing anxiety had almost doubled, at 24% (95% CI 23–26%) compared with a pre-pandemic level of 13% (95% CI 12–14%). In both studies, anxiety and depression during the pandemic was greater in younger members, women, those with pre-existing mental/physical health conditions and individuals in socioeconomic adversity, even when controlling for pre-pandemic anxiety and depression. Conclusions: These results provide evidence for increased anxiety in young people that is coincident with the pandemic. Specific groups are at elevated risk of depression and anxiety during the COVID-19 pandemic. This is important for planning current mental health provisions and for long-term impact beyond this pandemic.